Data integration for XML based on semantic knowledge - Ahmad, Kamsuriah; Mamat, Ali; Ibrahim, Hamidah; Mohd Noah, Shahrul Azman (2004)
Reconciling of knowledge from multiple heterogeneous data sources has been a major focus of database research for more than a decade.As a standard for exchanging business data on the WWW, XML should provide the ability of expressing data and semantics among them. Since most of application data are stored in relational databases due to its popularity and rich development experiences over it.Therefore, how to provide a proper mapping approach from relational model to XML model becomes the major research problem in the field of current information exchanging, sharing and integration..The model needs to be integrated and at the same time maintain the semantic knowledge among the data. The aim of this paper is to provide an overview for XML based data integration on semantic knowledge.At the end of the paper, we review some methodologies from existing literature.